Expo '70 - U.S. Pavilion (Nippon Beauty Card Center, Inc.)
A cable-roofed dome in the left is the U.S. Pavilion whose biggest attraction is the display of moon rocks brought to earth by the Apollo 11. Also seen in the picture are (from left to right) Electrium, Australian Pavilion, Furukawa Pavilion, Soviet Union Pavilion, British Colombia (Canada) Pavilion, German Pavilion and Quebec (Canada) Pavilion.